Variability of body mass and urine specific gravity in elite male field hockey players during a pre-Olympic training camp - Vescovi, J. D.; Watson, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
This field-based observational study was designed to examine the intraindividual variation of first morning body mass and urine specific gravity (Usg) in male hockey players (n = 22) during a 10-day training camp. It was also designed to evaluate the prevalence and interrelationship of morning hypohydration and postmatch dehydration using Usg and changes in body mass, respectively. Body mass and Usg were measured upon waking; body mass was also measured before and after matches. Individual means, SD, and coefficient of variation (CV) were calculated for morning body mass and Usg using 3, 6, and 8 days. Daily prevalence for euhydration and postmatch dehydration using morning Usg (<1.020) and changes in body mass (>-2%), respectively, were determined. Measurement of morning body mass and Usg for 3 days had low variability (CV < 1%) with no improvement at 6 or 8 days. Between 36% and 73% of players were considered euhydrated based on morning Usg. Postmatch body mass was reduced >1% in 50-85% of players, with up to 40% experiencing changes >-2%. Postmatch changes in body mass were unrelated to Usg the subsequent morning. These outcomes can be helpful in establishing criteria for detecting meaningful changes in morning body mass and Usg in similar settings, helping to monitor hydration status in elite male athletes. Despite ample fluid availability and consumption, many players experienced hypohydration and dehydration during the camp, indicating that careful monitoring and an individual fluid replacement approach are warranted in these environments.